The influence of attitudes and contextual factors on entrepreneurial intentions of students - Dahlan Dahlan; Ibrahim Syah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to determine and analyze the Influence of Attitudes and Contextual Factors on Entrepreneurial Intentions of Management Students at Maros Muslim University. The sample in this study were all final year management students totaling 100 people. Data was obtained from a questionnaire instrument which was distributed and processed using Partial Least Square (PLS) software. This study found that attitudes with indicators of risk-taking, originality, future-oriented, task and result-oriented, only originality and future-oriented had no significant effect on entrepreneurial intentions, while the indicators of contextual variables consisted of academic support, relational support and structural support all have a significant influence on the entrepreneurial intention of students. In addition to trying to cultivate an entrepreneurial character, it is also very important to have full support from the world of education, family and policies from the local environment. It is necessary to provide entrepreneurship skills that are more intensive from the academic world, and support from the government with policies that are able to encourage the intentions of prospective entrepreneurs to realize their business plans.